Parastomal Hernia Repair Using a Silo Biologic Mesh. Issue 5 (November 2021) - Chegireddy, Vishwanath; Doval, Andres F.; Zavlin, Dmitry; Ellsworth, Warren A.; Dinh, Tue A.
Abstract : Background: A parastomal hernia (PSH) is an enlargement of the stoma's original opening through the abdominal wall's musculature around a colostomy, ileostomy, or urostomy. Its incidence can be up to 48%. The described methods for its repair have high recurrence rate. This article presents a 3-dimensional silo technique for PSH repair (PSH-R). The aims of this technique are to enhance the structural strength of the tunnel wall, to reinforce both the sidewalls and the fascia above and below the muscular opening, and to maintain a stable stoma opening. Methods: All consecutive patients undergoing PSH-R with the silo technique between January 2009 and May 2018 by 2 plastic surgeons were included. The outcome parameters of interest were hernia recurrence and wound-related complications. Results: This study reports 22 patients (9 male, 13 female) with a mean age of 66.7 years and an average body mass index of 29.2. The variety of ostomy types included 10 colostomies, 7 ileostomies, and 5 urostomies. Postoperatively, there were 3 surgical site infections, 1 seroma, and 2 wound healing delays. Six patients were readmitted, 3 of those because of small bowel obstruction. These 3 cases all required reoperation, in addition to 1 operative revision for stoma retraction. During our average follow-up of 19.9 months, 3 cases of PSH recurrence were diagnosed for a recurrence rate of 13.6%. Conclusions: This silo technique is associated with favorable complication and low recurrence rates compared with the available techniques in surgical literature. In our practice, it has established itself as a new and safe technique for complex or recurrent PSHs and should be considered in a surgeon's armamentarium. This technique has become our standard for treatment of recurrent PSHs.